Etos i profesjonalizm w trosce o godność pacjenta - Prüfer, Paweł (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
In the social and medical sciences, especially recent time, there has been a broad and multi-problem interest in issues related to the patient, his psychophysical condition and sense of well-being. A recently published publication on the psychosocial determinants of patient care, prepared with great care by the authors and the editors, essentially representing medical sciences, is a valuable example of this interest. This text is an attempt to present the mentioned monograph, primarily to extract and show its cognitive and practical values. The text also contains a somewhat polemical perspective regarding some decisions and analyses. For the most part, however, it is an attempt – taking the form of a review article – to positively present the great values of this scientific, interpretive endeavor, emphasizing the many potential benefits of reading the volume and attempting to use it in medical practice and in the management of medical entities. The presence of axiological elements in the contents of the book is also not overlooked.